The impact of rebranding on fox comedy - Fontes, Francisco Xavier Moura Borges Ribeiro de (2017)
In the context of the Portuguese television market, this thesis aims to quantify the effects of rebranding on Fox Comedy. We find that, on average, rebranding results in a 0,05% increase in the share of audience, indirectly influencing the share of investment in advertising, by producing effects in different variables of the TV channel. Moreover, we provide a forecasting model for the share of investment in advertising, where we tackle the jump in the time series data carried out by the rebranding process. The predictions are of a 3 p.p. increase within the next 12 months.